Face and content validation of the amyotrophic lateral sclerosis—Bulbar dysfunction index (ALS-BDI) - Yunusova, Yana; Waito, Ashley; Barnett Tapia, Carolina; Huynh, Anna; Martino, Rosemary; Abrahao, Agessandro; Pattee, Gary L.; Berry, James D.; Zinman, Lorne; Green, Jordan R. (Frontiers in Neurology, 2023)
Purpose Early detection and tracking of bulbar dysfunction in amyotrophic lateral sclerosis (ALS) are critical for directing management of the disease. Existing physiological assessments of bulbar dysfunction are often inaccessible and cost-prohibitive for clinical application. Existing clinical assessments are limited. The overall goal of our research is to develop a brief and reliable, clinician-administered assessment tool, the ALS Bulbar Dysfunction Index (ALS-BDI) to evaluate bulbar dysfunction. The aim of this study was to establish content and face validity of the ALS-BDI through item generation and reduction, including item scoring. Methods The design of the ALS-BDI followed guidelines outlined by the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN). The design stage of the ALS-BDI involved two steps: (Step 1) the generation of candidate items from a literature review of commonly used clinical tools, and selection of items following a review of item reliability and item relevance and expert consensus; (Step 2) the assessment of their content and face validity via online survey feedback from experts (n = 35). The initial design was followed by a semi-structured cognitive interview with Speech-Language Pathologists (n = 5) to finalize a testable draft of the instrument. Results Two drafts of the ALS-BDI were developed. The first draft contained 48 items, after a review of existing clinical tools for their relevance to bulbar dysfunction in ALS. Of the 48 items, 35 items were retained after surveying experts and clinician users for their relevance, feasibility, interpretability, and appropriateness. The second draft of the ALS-BDI contained 37 items, due to one item splitting, based on users cognitive interviews. Conclusions The ALS-BDI described in this study aims to provide a brief and reliable, clinician-administered assessment tool to evaluate bulbar dysfunction in patients with ALS. Future research will evaluate the psychometric properties of this tool including its reliability, validity, and responsiveness to change over time.